Artificial Intelligence in Civic Education Finding a Balance between Technology and Teacher Roles - Muhammad Iqbal Baihaqi; Neni Fitriawati; Intan Sukmasakti Suwarno Putri; Yusri Karmila; Siti Munaziroh (Inovasi Analisis Data, 2024)
Objective: This study examines the role of Artificial Intelligence (AI) as both an innovative tool and a challenge in citizenship education at Islamic Vocational School Kanigoro. It aims to provide insights into how AI impacts educational practices, student engagement, and learning outcomes.Methods: A qualitative approach was employed, utilizing observations and interviews to gather data from teachers and students. This method allowed for an in-depth exploration of the dynamics and implications of AI integration in the classroom.Results: The study found that AI technologies, such as Quizizz and Kahoot, were effectively used to automate administrative tasks and personalize learning experiences, significantly improving educational efficiency and student engagement. AI-driven platforms provided tailored instructional content and rapid assessments, enhancing teaching methodologies and learning outcomes. However, challenges such as over-reliance on AI, privacy concerns, and potential algorithmic bias were identified.Conclusion: This study highlights the transformative potential of AI in citizenship education while underscoring the importance of balancing technological innovation with human interaction. Effective integration of AI can enhance learning experiences and foster critical thinking and ethical reasoning among students. The findings advocate for continuous professional development for educators, ethical AI practices, and the preservation of human-centric educational values. Future research should explore diverse educational contexts to further understand the benefits and challenges of AI in education